FAVQULODDA VAZIYATLARDA TO‘SINLARDAGI EGILISH DEFORMATSIYASINI VA NОRMAL KUCHLANISHNI HISOBLASH - E.Vassiyev (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The article shows the determination of bending deformation and normal stress in beams in case of emergency situations. In pure bending, the bending moment and shear force in the cross-sections of the beam are presented. In emergency situations, the normal stress of any point lying on the cross section of the purely bent beam was calculated. The static moment of the cross-sectional surface of the beam relative to the neutral axis is given. The moment of resistance was calculated using the geometric characteristics of the cross-section, and the bending strength of the beams.